Puerarin Exerts an Antiinflammatory Effect by Inhibiting NF‐kB and MAPK Activation in Staphylococcus aureus‐Induced Mastitis. (23rd June 2016) - Wu, Haichong; Zhao, Gan; Jiang, Kangfeng; Chen, Xiuying; Zhu, Zhe; Qiu, Changwei; Deng, Ganzhen
Abstract : Mastitis is defined as the inflammation of the mammary gland. There is generally no effective treatment for mastitis in animals. Puerarin, extracted from Radix puerariae, has been proven to possess many biological activities. The present study aims to reveal the potential mechanism that is responsible for the antiinflammatory action of puerarin in Staphylococcus aureus ( S. aureus )‐induced mastitis in mice. Histopathological changes showed that puerarin ameliorated the inflammatory injury induced by S. aureus . Quantitative real‐time polymerase chain reaction and ELISA analysis indicated that puerarin not only suppressed the production of pro‐inflammatory cytokines such as TNF‐α, IL‐1β, and IL‐6 but also promoted the secretion of IL‐10. Toll‐like receptor 2 (TLR2) is important in the immune defense against S. aureus infection. Research in molecular biology has shown that the expression of TLR2 was inhibited with administration of puerarin. Further studies were performed on NF‐kB and mitogen‐activated protein kinase signaling pathways using western blot. The results demonstrated that puerarin suppressed phosphorylated IkBα, p65, p38, extracellular signal‐regulated kinase 1and 2 (ERK), and c‐Jun N‐terminal kinase (JNK) in a dose‐dependent manner. All of the results suggested that puerarin may be a potential therapy for treating mastitis. Copyright © 2016 John Wiley & Sons, Ltd.